249 A SURVEY OF IRISH DOCTORS VIEWS ON FLEXIBLE TRAINING. (18th November 2021) - Loughlin, E; McNamara, R; Antonenko, A; O'Regan, A; O'Connor, M
Abstract: Background: We aimed to establish the views of non consultant hospital doctors working in Ireland on the options available for 'Flexible Training' or 'Less-Than-Full-Time-Training'. Our population is ageing rapidly, and an expanding workforce will be required. Difficulties with doctor retention and recruitment are growing challenges in Ireland. Methods: An anonymised survey of 9 questions was carried out using Survey Monkey®. Question format included multiple choice, yes/no or a free text box. This was disseminated via the Royal College of Physicians of Ireland to 1, 557 trainees of the Institute of Medicine, the national postgraduate body for medical specialties. It was also circulated to members of the Irish Medical Organisation, the national medical organisation, and to approximately 200 doctors across two hospitals on social media. Results: There were 674 (84.3%) respondents in training- 46.3% BST, 53.7% HST; and 125 (15.6%) non-training respondents. Doctors overwhelmingly felt trainees should have access to flexible training (n = 849, 99.41%), with 82.39% reporting they would apply (n = 702). Most (92.5%) felt that 16 WTE positions was inadequate (n = 789). Reasons chosen for not applying for flexible training included- 36.1% (n = 169) felt it could impact their career, 25.4% (n = 119) identified they did not meet the criteria, 14.32% (n = 67) reported no interest, while 24.1% (n = 113) gave 'other' reasons including lengthy training, salary impacts, and not having a requirement for flexible training. When asked about suggestions for improving flexible training, 19.7% chose 'offer more places', 6.7%-'remove eligibility criteria', 19.6% -'offer job sharing options', 9.5%- 'allow more flexible training years', 17.7% -'regional based training', 22.5% -'all of the above', 4.9%—'other'. Conclusion: Our survey suggests non consultant hospital doctors in Ireland strongly desire an expansion of current flexible training options. This is essential to ensure Ireland is an attractive place for doctors to work, to support their health and wellbeing, and to ensure an adequate workforce to care for an ageing population.